Media Agar Tepung Kacang Hijau, Kacang Merah, Kacang Tunggak, Kacang Kedelai Sebagai Media Kultur Jamur Aspergillus Flavus - Anik Nuryati; Sujono Sujono (POLTEKKES KEMENKES YOGYAKARTA, 2017)
Sabouraud Dextrose Agar (SDA) is a medium for the growth of fungi, ready to use, packaged in 500 gr, expensive, hard to find and takes a long time to obtain so it needs alternative media. SDA contains 4% glucose. The use of mung bean, red bean, cowpea and soy bean flour as culture media has never been done. The material contains high protein and high vegetable oil, allowing Aspergillusflavus to grow in it. The research aimed to know whether mung bean , red bean, cowpea, soy bean flour agar media may be used as culture media on the growth of Aspergillus flavus, and to know the diameter and color of colonies. Subjects were Aspergillusflavus fungus, inoculated in SDA media with incubation time 24 hours. Macroscopic shape: filamentous colonies, clear. Microscopic: insulated hyphae, branching, there are vesicles with conidia arranged like a fan. The object of the research are mung bean, red bean, cowpea, and soybean flour obtained from the manufacture of good quality peanut flour, whole seeds, not rancid, not wormy. Method: This research is an experimental study. The treatment was given to the independent variable and then measures the dependent variable. The result shows that mung bean, red bean, cowpea, soy bean flour agar media can be used as culture media on the growth of Aspergillusflavus fungus. Diameter of colony growth to five days on soybean flour agar medium was 7.1 cm, it was greater than red beans media 6.1 cm, mung bean media 6.7 cm and SDA 6.5 cm. Colony color on all media are white, turns yellow and then green and dark green until the end. It can be concluded that Aspergillus flavus fungus can grow on mung bean, red bean, cowpea, soy bean flour agar media with various diameters.